A STUDY ON SOIL-LIKE MATERIAL OBTAINED FROM LANDFILL MINING - Mohammed Najamuddin; Ahmad Mamdouh Mohammad Sabbah; Zeeshan Firdous (International Journal of Innovations in Engineering Research and Technology, 2021)
This study aims at understanding the engineering properties of soil-like-material (SLM) obtained from landfill mining and its feasibility to be reused in multiple potential directions. The engineering properties of the material are taken from the researchers. This study compares the properties of soil-like material (SLM) with the properties of local soil. Leaching of heavy metals from soil-like material is analyzed to understand the contamination levels. Properties like organic content, release of dark colour leachate and amount of soluble salts are analyzed in comparison to local soils. From geotechnical characterization of SLM, it is found that SLM is non-plastic with low specific gravity due to presence of organic material. The strength properties are found to be satisfactory and permeability is similar to that of local soil. From the laboratory test results, it is found that the SLM is not hazardous. It is not similar to local soil. It is not inert and hence the unrestricted re-use of SLM is avoided. Treatment techniques and design measures can be adopted and SLM can be used in various applications.